ANALISIS PERJANJIAN SEWAMENYEWA SAFE DEPOSIT BOX (KOTAK PENYIMPANAN BARANG/SURAT BERHARGA) DI PT BANK MANDIRI (PERSERO) TBK PEKANBARU - Maylia Darwita; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Safe Deposit Box is a bank services system for people that bank leases the box with size and period of time to protect valuable things. PT Bank Mandiri (Persero) Tbk Pekanbaru is a bank does business to provide a place toprotect thing and marketable securities. Safe Deposit Box leasing service in PT Bank Mandiri (Persero) Tbk Pekanbaru regulates by The Safe Deposit Box Leasing Ttreaty and General Term of Safe Deposit Box Leasing between PT Bank Mandiri (Persero) Tbk Pekanbaru and customer to obey Article 1548 Indonesia Civil Code about leasing.The purpose of writing this thesis are: first, to know regulation about Safe Deposit Box in Indonesia Law. Second, to know the right and obligation of customer and the Bank from Safe Deposit Box Leasing Treaty what is suitable with the Third Book of Indonesia Civil Code. And Third, to know PT Bank Mandiri (Persero) Tbk Pekanbaru’s responsibility for things inside Safe Deposit Box.Kind of this study can classified as normatif-emphiric study, becuase in this study, writer analysize the Safe Deposit Box Leasing Treaty and investigate in place according problem directly. This study does in PT Bank Mandiri (Persero) Tbk Pekanbaru used data source, are primary data and secondary data, technique of data collect in this study is literature study and interview with bank party as a party of leasing and customer party as Safe Deposit Box lessee.Based on the results of study, there are three main points can be summarised. First, there is no the regulation focus to regulate how Safe Deposit Box is regulated and other technical points in Indonesia thus PT Bank Mandiri (Persero) Tbk Pekanbaru make treaty with the customer to use legal norm of leasing treaty in practice. Second, PT Bank Mandiri (Persero) Tbk Pekanbaru obligation is not regulated in Safe Deposit Box leasing treaty and also in General Term of Safe Deposit Box Leasing. Third, PT Bank Mandiri (Persero) Tbk Pekanbaru do not responsible for thing inside Safe Deposit Box if thing brokes or losts, because it had appointment by the parties in standard clausula form.JOM Fakultas Hukum Volume III Nomor 2, Oktober 2016 Page 2Writer recomendation is: first, it needs the Safe Deposit Box regulations in order to implement Safe Deposit Box leasing treaty between the Bank and the customer to avoid confusing in implement. Second, the Bank must notice customer interest and not more concerned with bank interest. Third, it needs increasing costumer protection using Safe Deposit Box and legal certainty of responsibility to lost thing inside Safe Deposit Box.Keywords: Safe Deposit Box, Leasing Treaty, PT Bank Mandiri (Persero) Tbk Pekanbaru.